Does Self-Employment Reduce Unemployment? - David B. Audretsch; Roy Thurik; André van Stel; M.A. Carree (Max Planck Institute of Economics, 2007)
This paper investigates the dynamic interrelationship between self-employment and unemployment rates. On the one hand, unemployment rates may stimulate start-up activity of self-employed. On the other hand, higher rates of self-employment may indicate increased entrepreneurial activity reducing unemployment in subsequent periods. These two effects have resulted in considerable ambiguities about the interrelationship between unemployment and entrepreneurial activity. This paper introduces a two-equation vector autoregression model capable of reconciling these ambiguities and tests it for data of 23 OECD countries over the period 1974-2002. The empirical results confirm the two distinct relationships between unemploy-ment and self-employment, i.e. "refugee" and "entrepreneurial" effects. We also find that the "entrepreneu-rial" effects are considerably stronger than the "refugee" effects.
Older version: http://hdl.handle.net/10419/19998
Keywords: J23; J64; L26; L53; M13; O11; 330; entrepreneurship; Gibrat's Law; self-employment; unemployment; Selbstständige; Beschäftigungseffekt; Arbeitslosigkeit; VAR-Modell; OECD-Staaten